Masyarakat Indonesia dan Tantangan Sejarah di Era Post-truth - Anwar Firdaus Mutawally; Mumuh Muhsin Zakaria; Hazbini Hazbini (KOLONI, 2023)
The development of information technology in the 4.0 revolution has led to an increasingly rapid and unstoppable flow of information. In addition, the development of Post-Modernism plays an important role in creating a new society called post-truth or post-truth which begins to challenge the existing truth. This study aims to investigate the challenges faced by Indonesian society regarding history in the Post-truth era along with the solutions offered. This research is a descriptive qualitative research technique using library research. The results of the study show that post-truth arises as a result of the development of post-modernism and changes in information systems. Even though the post-truth era is relatively new in Indonesia, it has had a major impact on historical science. Therefore the solution offered is the active role of historians and history educators in disseminating history, increasing literacy for the public, and increasing historical awareness to avoid false information, especially related to a historical event.  Keywords: Society, Indonesia, History, Post-truth